The Causal Attributions of Poverty: The Case of Ordu University - Mehmet Koca (İnsan & Toplum)
Casual attribution is the explanations of individuals that attribute reasons to events or situations that they or other people have encountered. The aim of this study is to determine the causal attributions of university students related to poverty. For this purpose, “Causal Attribution for Poverty Scale” was used in the study. 485 undergraduate students from Ordu University participated in this study and participants were selected according to random sampling technique. SPSS program was used for the data analyses. Comparisons between groups were made with t-test and ANOVA analysis, Scheffe test was used to determine which differences between groups were, Pearson correlation analysis was used to reveal relationships between variables. According to the findings obtained from these analyzes, the causal attribution levels of the students regarding the general poverty were high, they made the most attribution to structural attributions. Among the structural, individualist, fatalist-familial attribution dimensions that exist to explain poverty in our society, and that was followed by the fatalist-familial and individualist attributions. In addition, based on some socio-demographic, socio-economic, political and psychological characteristics of the participants, evaluations were made on the causal attribution levels of poverty.